Molécula de dano renal-1 na urina e sua associação com o controle glicêmico e com a concentração urinária das interleucinas 1 e 6 no diabetes tipo 2 - Bollick, Yãnaí Schneider (2018)
Diabetes kidney disease (DRD) is among the main and most relevant complications of diabetes mellitus (DM). Hyperglycemia and inflammation are two of several factors involved in the development and progression of DM complications, including DRD. The Kidney injury molecule-1 (KIM-1) is a urinary biomarker indicative of tubular renal injury and has been studied along with other markers in the search for an early diagnosis of renal pathologies, since studies suggest that the tubular lesion appears before even from the kidney undergoes glomerular damage. Increased levels of KIM-1 in urine have been demonstrated in hyperglycemic states and also in diabetic individuals with renal inflammation. Further, with regard to inflammation, the interleukin-1 (IL-1) and interleukin-6 (IL-6) proinflammatory urinary cytokines may be useful for the evaluation of DRD. Considering the consequences that the glycemic control and the inflammatory process can cause in the development of DRD, the present study analyzed the association of urinary levels of KIM-1 with levels of glycated hemoglobin (HbA1c) and renal inflammation, through urinary cytokines IL- 1 and IL-6 in patients with type 2 DM. This study included 122 patients with type 2 DM divided into two groups according to the median urinary KIM-1, represented by ≤87 pg / mL and> 87 pg / mL . Urinary levels of KIM-1, IL-1 and IL-6 along with other biochemical parameters were evaluated in these patients. Patients were further divided into HbA1c quartiles, where urinary KIM-1 values increased by 34% in patients with HbA1c above 8.7% compared to patients with values below 6.0%. Similarly, stratifying patients in quartiles of IL-1 and IL-6, urinary levels of KIM-1 also increased approximately 130% and 90%, respectively. Positive correlations were observed between urinary KIM-1 and HbA1c (r = 0.23, P = 0.028), urinary KIM-1 and urinary IL-1 (r = 0.60, P <0.001) and urinary KIM-1 and IL -6 urinary. (r = 0.40, p <0.001). Urinary KIM-1 levels were higher among patients with type 2 DM who had the highest levels of HbA1c and the proinflammatory cytokines IL-1 and IL-6 in the urine. Thus, low glycemic control and renal inflammation contribute to the occurrence of tubular damage in type 2 diabetes, and KIM-1 has been shown to be a useful marker in detecting tubular damage in patients with type 2 diabetes.